Inflation in the shadow of debt: growth, regulations, and reforms - Cochrane, John (Henry Stewart Talks, 2022)
Inflation, Economic regulation, Long-term debt, Taxation, Economic growth, Microeconomic reform, The fiscal theory of the price level